A new species of Ceratophysella (Collembola: Hypogastruridae) from Japan, with notes on its DNA barcode and a key to Japanese species in the genus - Nakamori, Taizo (Zootaxa, 2013)
Ceratophysella comosa sp. nov. was collected from ascomata of Ciborinia camelliae in Japan and the morphological and molecular characteristics of the species are described here. The species has 3 + 3 cephalic spines as in Ceratophysella loricata and Ceratophysella pilosa, but a plurichaetosis intermediate between C. loricata (absent) and C. pilosa (strong). The new species can be distinguished from these two species also by the number of setae on the first thorax segment and ventral tube. Partial DNA sequences of the mitochondrial cytochrome c oxidase subunit 1 (COI) gene were used as DNA barcodes to dis-tinguish species. Interspecific genetic distances of the gene were higher than the intraspecific distances between Ceratophy-sella species for which sequence data are available. An identification key of Japanese Ceratophysella is provided.